Characterisation of the Elastin Binding Protein (EbpS) of Staphylococcus aureus - Roche, Fiona M. (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Microbiology, 2001)
Staphylococcus aureus expresses an array of surface proteins that promote interaction of the bacterium with the host. Some surface proteins promote binding to components of the host extracellular matrix and can act as adhesins. Others bind proteins in plasma and may interfere with host defenses. Recently it has become apparent that some surface proteins can bind two or possibly more ligands. This thesis describes an unusual membrane associated surface protein of S. aureus that promotes interactions with elastin.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin